Uzbek Opposition Version of the Modern Slang used between English Youth - Choriyeva Nilufar Komil Kizi (Researchparks Publishing, 2022)
This article discusses the selection and study of alternative versions of modern slangs, which are used among young people in England today. The article also provides a practical study of modern slang used among young English people.